EFFECTS OF NON-IRRIGATION CROP ROTATION ON WEED DYNAMICS - Saikhantsetseg S; Ganbold N; Nambar J; Sodgerel P (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
Crop rotation is very important with regards to productivity. In fact, the aim of crop rotation is increased productivity. This is achieved by overall benefits of crop rotation, such as better soil quality, reduced pests and weed control by breaking their life cycles. Weed competes with crops for light, nutrients and moisture. The impact of weeds on crop yield varies according to the weed species present, biological characteristic, their density, distribution and their persistence during the cropping cycle. In dry, arid Mongolian condition, due to increased number of mechanical cultivation of soil for controlling weed, soil fertility is decreasing and effected by erosion. Hence, agro-ecosystem is unstabilised. Therefore, for reducing erosion effect and stabilizing agro-ecosystem. So, for those who aim at conserving soil fertility and reducing soil erosion, this is an impelling task to study effects of crop rotation on weed density and diversity, identify and select right predecessor crops for effective weed control. As a result the determination of weed density before planting in 2, 3 and 4 field rotations revealed more perennial weed infestation of 4 field rotations than 2 and 3 field rotations. Perennial weed population largely composed of Agropyron repens, Nonea Pulla, Cirsium Arvense, Potentilla Anserina and Linaria vulgaris. Fields tend to be increasingly subject to perennial weed infestation as the crop sequence gets lengthier. 21-80 fewer weed plants were found in wheat after fallow (fallow-wheat rotation), compared to 3 and 4 field rotations. Estimated wheat yield was 0.22-0.34 t/ha higher, in contrast to other crop sequences. Weed density in second wheat grown in continuous cropping system gets higher, resulting in reduced yield, which suggests wheat as not ideal pre-crop.